2019
DOI: 10.1007/s11420-019-09702-1
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Physical Performance Tests in Individuals with Advanced Knee Osteoarthritis

Abstract: Background Individuals with advanced osteoarthritis (OA) of the knee experience significant impairments in balance and in essential physical functions such as walking and rising from a chair. There is limited evidence on valid outcome measures to capture these impairments. Questions/Purposes We sought to examine the construct validity of three physical performance measures in patients with advanced knee OA: a gait speed (GS) test, the Short Physical Performance Battery (SPPB), and the Timed Up and Go (TUG) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 46 publications
1
14
1
Order By: Relevance
“…In general, clinical-functional scores of patients in the present study are not different from values available in other studies on knee OA patients for KSS [37][38][39] and for SPPB [40][41][42]. Also, knee OA as radiologically measured by means of the Kellgren-Lawrence score resulted in correlation to the average Stability Index in the open eyes trial, suggesting that a worse functional performance is present in more severe radiological OA.…”
Section: Discussioncontrasting
confidence: 50%
“…In general, clinical-functional scores of patients in the present study are not different from values available in other studies on knee OA patients for KSS [37][38][39] and for SPPB [40][41][42]. Also, knee OA as radiologically measured by means of the Kellgren-Lawrence score resulted in correlation to the average Stability Index in the open eyes trial, suggesting that a worse functional performance is present in more severe radiological OA.…”
Section: Discussioncontrasting
confidence: 50%
“…Six multi-activity measures were the SPPB, 34 the Performance Tests Measures (PerF), 30 Physical Activity Restrictions (PAR), 32 Timed Assessment, 11 Aggregated Locomotor Function (ALR), 33 and Iowa Level of Assistance Scale (ILAS). 31…”
Section: Resultsmentioning
confidence: 99%
“…When applied in mild to moderate patients, it showed sufficient reliability, 17 and when used in ES or postoperative patients, it showed sufficient hypothesis testing and responsiveness. 23,34 However, this test may not be sensitive enough to reveal early signs of functional decline. 54 Other tests and multi-activity measures…”
Section: Sit-to-stand Testsmentioning
confidence: 99%
“…Further investigation may be needed in this area due to research findings with mixed results. For instance, a prior study found that among older people, both self-reported and objective measures of physical functioning were associated with disability onset [ 39 ], whereas another study among people with knee osteoarthritis found physical performance test measures correlated poorly with self-reported measures [ 40 ]. For the last significant need factor, total number of prevalent chronic health conditions, since having more chronic conditions was associated with reporting a functional limitation, this suggests the potential benefit for healthcare providers to recommend older adults with five or more chronic conditions to undergo physical performance tests.…”
Section: Discussionmentioning
confidence: 99%